INTEGRASI TIM SEPAK BOLA PADA PELATIH DALAM SUDUT PANDANG SOSIOLOGI OLAHRAGA - Zahrotunnisa Noviriyanti; Dwi Muhammad Riski; M. Naufal Dzaky Immamughni Alwasi; Melani Agustina; Gabriela Talasari S; Muhammad Fajri; Muhammad Rizky Firdaus; Pardiman Pardiman; Ibnu Sina; Nazwa Zahralova (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to examine the role of sport sociology in the practice of coaching and leadership of soccer coaches, especially in the context of multicultural teams. Through a qualitative approach and in-depth interviews with a number of soccer coaches, it was found that understanding the social background, culture, and individual values ​​of players is very important in creating effective interpersonal relationships in the team. The results showed that coaches who have intercultural communication skills and adaptive leadership styles tend to be successful in building strong social cohesion and solidarity among players. Social integration in a soccer team is a dynamic process, where the coach acts as a socialization agent who is able to balance diversity without causing internal conflict. These findings contribute to the development of more inclusive and socially value-oriented coaching strategies. This study also emphasizes the importance of coaching training that includes social and cultural aspects in the management of modern sports teams.